2015
DOI: 10.1016/j.acclit.2015.09.001
|View full text |Cite
|
Sign up to set email alerts
|

A review of meta-analytic research in accounting

Abstract: Please cite this article as: Khlif, H., and Chalmers, K.,A review of metaanalytic research in accounting, Journal of Accounting Literature (2015), http://dx. AbstractThis study reviews the use of meta-analysis in accounting research. We categorize the metaanalytic research into five topics: financial reporting, auditing, corporate governance and accounting quality, management accounting, and miscellaneous topics. Further, we classify the studies by the meta-analysis technique employed: Hunter et al. (1982) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
86
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 57 publications
(87 citation statements)
references
References 45 publications
1
86
0
Order By: Relevance
“…These restrictions in vote counting and narrative literature reviews might be overcome by the use of quantitative meta-analysis (Combs et al 2011). Although meta-analyses are not very common in management control and corporate governance research, we found that an increasing number have been published over the years (Byron and Post 2016;Endrikat et al 2020;Khlif and Chalmers 2015). As there are very conflicting results from empirical-quantitative studies in sustainable corporate governance research, meta-analyses statistically summarise existing research and increase the quality of results compared with literature reviews.…”
Section: Literature Review Methodologymentioning
confidence: 89%
See 1 more Smart Citation
“…These restrictions in vote counting and narrative literature reviews might be overcome by the use of quantitative meta-analysis (Combs et al 2011). Although meta-analyses are not very common in management control and corporate governance research, we found that an increasing number have been published over the years (Byron and Post 2016;Endrikat et al 2020;Khlif and Chalmers 2015). As there are very conflicting results from empirical-quantitative studies in sustainable corporate governance research, meta-analyses statistically summarise existing research and increase the quality of results compared with literature reviews.…”
Section: Literature Review Methodologymentioning
confidence: 89%
“…As there are very conflicting results from empirical-quantitative studies in sustainable corporate governance research, meta-analyses statistically summarise existing research and increase the quality of results compared with literature reviews. Furthermore, meta-analyses can include relevant moderator analysis across multiple studies Khlif and Chalmers 2015). If a reasonable number of studies exists on our research topic, we suggest performing quantitative meta-analyses of the impact from CSR committees and CSOs on CSR-related and/or financial outputs.…”
Section: Literature Review Methodologymentioning
confidence: 99%
“…The purpose of SLRs is to provide an overview of existing knowledge on the research topic and provide insight into its development (Khan, Hassan, Harrison, & Tarbert, 2020; Khlif & Chalmers, 2015). According to Fink (2005, p. 3), the SLR is ‘a systematic, explicit, comprehensive, and reproducible method for identifying, evaluating, and synthesising the existing body of completed and recorded work produced by researchers, scholars, and practitioners’.…”
Section: Methodsmentioning
confidence: 99%
“…Unlike literature reviews on ARL that summarize prior research, irrespective of the quality of its publication outlets, meta‐analysis is often used to summarize prior research findings that seem mixed. It seems appropriate to apply meta‐analysis to the ARL setting, to reconcile the conflicting findings across countries and jurisdictions (Hay, Knechel, & Wong, ; Hwang & Lin, ; Khlif & Chalmers, ; Lin & Hwang, ). In particular, we test for the presence or absence of publication bias using a meta‐regression analysis technique (Hay & Knechel, ).…”
Section: Introductionmentioning
confidence: 99%
“…Despite the importance of conducting meta‐analysis, there has been little such research in the accounting discipline, and particularly in the subdiscipline of auditing. Khlif and Chalmers () identified 27 previous meta‐analyses in the accounting discipline, with only seven in the area of auditing. Prior meta‐analyses in auditing include Trotman and Wood () on internal control evaluation judgements by different auditors, Kinney and Martin () on audit‐related adjustments and pre‐audit earnings and assets, Hay et al () and Hay () on client, auditor, and engagement attributes and audit fees, Lin and Hwang () on audit quality and earnings management, Habib () on nonaudit fees (NAFs) and accounting information quality, and Habib () on the determinants of audit opinion decisions.…”
Section: Introductionmentioning
confidence: 99%